Naca Journal - Volume one. - Amenoff, Gregory; Cibic, Aldo; Danoff, Michael; Donnelly, Brian; Hershman, Lynn; Hess, Donald M.; Hosoe, Isao; Imaï, Toshimitsu; Kurchart, Maria; Lacy, Suzanne; Maler, Leopoldo M.; Reichardt, Jasia; et al. (Napa : NACA (Napa Contemporary Arts Foundation), 1992)
Amenoff, Gregory ; Burchfield, Charles Ephraim ; Ryder, Albert P. ; Hartley, Marsden ; Yoakum, Joseph ; Judd, Donald ; Nauman, Bruce ; Hesse, Eva ; Winsor, Jackie ; Shapiro, Joel ; Imaï, Toshimitsu ; Lacy, Suzanne ; Kaprow, Allan ; Ukeles, Mierle Laderman - ; Simonds, Charles ; Kriesche, Richard ; Hershman, Lynn
Engels
boek